2011
DOI: 10.1111/j.1365-2427.2011.02629.x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the impact of demographic factors on population differentiation of an endangered freshwater crayfish (Austropotamobius pallipes) using population density and microsatellite data

Abstract: 1. Habitat fragmentation of stream ecosystems often results in decreased connectivity between populations and lower population sizes. Hence, understanding how habitat fragmentation affects genetic erosion is important for the preservation of freshwater biodiversity, in particular, as small populations suffer from loss of genetic diversity through genetic drift and loss of fitness because of inbreeding, increasing the risk of extinction. 2. Here, we assess the impact of demographic factors on population differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…This is consistent with other freshwater crayfish (Fetzner & Crandall 2001, Baric et al 2006, Gouin et al 2011) and may be attributed to an inherent tendency to inbreed due to poor dispersal ability and small population size. Other factors such as male dominance hierarchies, commonly observed in freshwater crayfish and other crustacean groups (Moore & Bergman 2005), will also act to reduce effective population sizes (N e ) and exacerbate the severity of inbreeding.…”
Section: Genetic Structure and Diversity Across The Species' Distribusupporting
confidence: 74%
See 1 more Smart Citation
“…This is consistent with other freshwater crayfish (Fetzner & Crandall 2001, Baric et al 2006, Gouin et al 2011) and may be attributed to an inherent tendency to inbreed due to poor dispersal ability and small population size. Other factors such as male dominance hierarchies, commonly observed in freshwater crayfish and other crustacean groups (Moore & Bergman 2005), will also act to reduce effective population sizes (N e ) and exacerbate the severity of inbreeding.…”
Section: Genetic Structure and Diversity Across The Species' Distribusupporting
confidence: 74%
“…Individuals are arranged into sites from which they were sampled following the order given in Table 1 (site codes are also derived from Table 1), and sites are pooled into regions (Victoria and South Australia) al. 2005, Baric et al 2006, Gouin et al 2011. The mitochondrial DN A analysis indicates that the high level of contemporary structuring is likely to be a relatively recent demographic feature, with 4 of the 5 Victorian sites sharing a single dominant haplotype due to historical gene flow and recent common ancestry.…”
Section: Genetic Structure and Diversity Across The Species' Distribumentioning
confidence: 99%
“…Such genetic similarity -within and between catchments across river and tributaries separated by over 2000 km of waterways -is rarely observed in freshwater species, and is atypical of freshwater crayfish (Gouin et al 2006;Gross et al 2013) given inherent dispersal limitations, and the dendritic, and often fragmented, nature of freshwater environments. Large population sizes and sufficient gene flow among local populations has likely helped maintain high levels of genetic diversity and suppress the influence of genetic drift (Frankham et al 2010;Allendorf et al 2013), with the observed average allelic richness and heterozygosity (r ¼ 3.23 and H E ¼ 0.53) being uncharacteristically high for freshwater crayfish (Fetzner and Crandall 2002;Gouin et al 2011;Miller et al 2014). In fact, populations of E. armatus harbour similar, or in some cases higher, levels of genetic variation compared to widespread and more vagile freshwater fish species inhabiting the MDB; such as golden perch (Macquaria ambigua) (Faulks et al 2010), Murray cod (Maccullochella peelii) (Rourke et al 2011) and Australian smelt (Retropinna semoni) (Taylor et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the median time to quasi‐extinction, the extinction threshold was based on estimates of effective population size from Gouin, Souty‐Grosset, Bórquez, Bertin, and Grandjean () for Austropotamobius pallipes (white‐clawed crayfish), an endangered European freshwater crayfish, as published data related to extinction thresholds of Faxonius species could not be obtained. For A. pallipes , estimates of effective population size were variable but ≤150 in most populations examined (Gouin et al, ), so the effective population size used in the models was 150. All models were run for 1000 iterations over 100 years.…”
Section: Methodsmentioning
confidence: 99%